Effect of Various NaCl Concentration on Corrosion of Steel in Concrete Produced by Addition of Styrofoam - Keleştemur, Oğuzhan; Yıldız, Servet (My University, 2005)
In this study, the corrosion of reinforced steel in the concrete samples with various concentrations of NaCl and with the addition of styrofoam which was replaced 15% of the aggregate volume in the concrete structure was investigated. Additionally, the change on the corrosion of steel in the concrete samples with styrofoam and/or with silica fume 10% in the cement volume was explored. Three groups of concrete samples containing various NaCl concentrations were prepared. In the first group, the samples were without any additional material, the second group was produced by addition of styrofoam (15%) and the third group of samples prepared with the addition of styrofoam plus silica fume (10%). The corrosion rates were measured according to the galvanic current method on the samples. The corrosion potentials have been measured by applying the ASTM-C-876-91 method for 90 days and using Cu/CuSO4 reference electrode. As a result of these experiments, it was found that the corrosion rate of steel in the concrete samples with styrofoam increased with the increasing of the portion of NaCl. However, the corrosion rate of steel in the samples decreased with the addition of silica fume.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Corrosion; Styrofoam; Silica fume; Reinforced concrete; Steel